Factors Associated with the Complications of Hysteroscopic Myomectomy - Mariana Patelli Juliani de Souza Lima; Lúcia Costa-Paiva; Luiz Gustavo Oliveira Brito; Luiz Francisco Baccaro (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2020)
Abstract Objective To evaluate the factors associated with complete myomectomy in a single surgical procedure and the aspects related to the early complications. Methods A cross-sectional study with women with submucous myomas. The dependent variables were the complete myomectomy performed in a single hysteroscopic procedure, and the presence of early complications related to the procedure. Results We identified 338 women who underwent hysteroscopic myomectomy. In 89.05% of the cases, there was a single fibroid to be treated. According to the classification of the International Federation of Gynecology and Obstetrics (Fédération Internationale de Gynécologie et d'Obstétrique, FIGO, in French),most fibroids were of grade 0 (66.96%), followed by grade 1 (20.54%), and grade 2 (12.50%). The myomectomies were complete in 63.31% of the cases, and the factors independently associated with complete myomectomy were the diameter of the largest fibroid (prevalence ratio [PR]: 0.97; 95% confidence interval [95%CI]: 0.96-0.98) and the classification 0 of the fibroid according to the FIGO (PR: 2.04; 95%CI: 1.18-3.52). We observed early complications in 13.01% of the hysteroscopic procedures (4.44% presented excessive bleeding during the procedure, 4.14%, uterine perforation, 2.66%, false route, 1.78%, fluid overload, 0.59%, exploratory laparotomy, and 0.3%, postoperative infection). The only independent factor associated with the occurrence of early complications was incomplete myomectomy (PR: 2.77; 95%CI: 1.43-5.38). Conclusions Our results show that hysteroscopic myomectomy may result in up to 13% of complications, and the chance of complete resection is greater in small and completely intracavitary fibroids; women with larger fibroids and with a high degree of myometrial penetration have a greater chance of developing complications from hysteroscopic myomectomy.